2021
DOI: 10.1017/s1431927620024769
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Imaging of Nanostructures in an Electrolyte with a Scanning Electron Microscope

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…not the electrolyte, it is often hard to interpret how and why the structure of the electrode changed during the degradation process. To overcome this limitation, operando liquid cells have been developed for STEM [151][152][153] and also for SEM [154] that permit structure/chemistry changes in the electrodes to be observed during electrochemical cycling in all forms of liquid electrolytes. For these liquid cells, the low mass/density of Li metal causes a contrast reversal in the experimental images that makes the identification and tracking of Li metal easily quantifiable [151].…”
Section: Statusmentioning
confidence: 99%
“…not the electrolyte, it is often hard to interpret how and why the structure of the electrode changed during the degradation process. To overcome this limitation, operando liquid cells have been developed for STEM [151][152][153] and also for SEM [154] that permit structure/chemistry changes in the electrodes to be observed during electrochemical cycling in all forms of liquid electrolytes. For these liquid cells, the low mass/density of Li metal causes a contrast reversal in the experimental images that makes the identification and tracking of Li metal easily quantifiable [151].…”
Section: Statusmentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t and are exploring the use of a commercial closed cell system (Figure 5(c)) with integrated flow and regular reference/counter electrodes [163] for operando electrochemical studies.…”
Section: (F))mentioning
confidence: 99%
“…Therefore, studies of operando characterizations at the solid–liquid interface ( i.e., in situ characterization under electrochemical reaction in the liquid phase) have recently received attention. In situ and in real space the morphology changes and surface reconstruction of a model Cu electrocatalyst on atomic scale during the electrochemical CO 2 reduction reaction (CO 2 RR) were observed with an electrochemical atomic force microscope (AFM) which enabled the direct observation of oxidized copper surfaces entering different morphological regimes when certain cathodic CO 2 RR potential ranges are set. , Indeed, using both cyclic voltammetry and in situ electrochemical STM, it was shown that the electrochemical signal and the roughening of its surface are well-related. , Recently, by using liquid cell transmission electron microscopy (TEM) and scanning electron microscopy (SEM), it was found that Cu 2 O nanocatalysts restructure under CO 2 RR conditions. These well-established operando technologies allow us to observe key information on catalytic behaviors by monitoring the changes in interfaces on an atomic scale.…”
mentioning
confidence: 99%